The importance of coordination in freestyle wrestling - Hartmann, B.; Fetz-Hartmann, A. (International Journal of Wrestling Science, 2012)
The social conditions governing the growth and development of today`s youth has changed in most of the developed countries. This primarily means that there is a lack of physical movement. The coordinative abilities are insufficiently trained in the childhood and adolescence. It is necessary to bring young children to any kind of sport, where they gain access to a variety of movement experiences. Wrestling coaches working with such young children can help them to develop coordinative abilities, which are necessary for technique formation in wrestling. In this report we will give you some information regarding coordination and how coaches can best train the different abilities. We will give a general view of coordination in wrestling training, and how you can develop the various components of coordination. We also reference the specific needs of different age groups and ability levels of the young wrestlers encountered in wrestling training.